GAS TURBINE ENGINES CONSUMING BIOGAS - Ясиніцький, Е.; Гупало, Р. (Proceedings of National Aviation University, 2012)
A problem of implementation of biofuel for power plants of big capacity was considered in this article. Up to date in the world practice a wide implementation of biogas plants of low and medial capacity are integrated. It is explained by the big amount of enterprises in which relatively small volumes of organic sediment excrete in the process of its activity. An emphasis of article is on that enterprises, which have big volumes of sediments for utilizing of which module system of medial capacity biogas plants are non-effective. The possibility of using biogas and biomethane as a fuel for gas turbine engine is described. The basic problems of this technology and ways of its solutions are indicated. Approximate profitability of biogas due to example of compressor station located nearby poultry factory was determined also. Such factors as process characteristics of engine with capacity of 5 MW, approximate commercial price for natural gas and equipment costs due to official sources of “Zorg Ukraine” company was taken into consideration. The necessity for providing researches on influence of biogas on the process characteristics of gas turbine engine and its reliability, constructing modern domestic purification system for biogas was shown.